TERRESTRIAL ELECTROMAGNETIC LOADING CREATED BY ELECTROMAGNETIC RADIATIONS OF CELLULAR BASE STATIONS - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The integrated system characteristic of electromagnetic safety of terrestrial radio electronic environment - terrestrial electromagnetic filling as the total equivalent power of electromagnetic radiations of the radio equipment, falling to unit of the area of considered territory is offered. The equations defining quantitative relationship of terrestrial electromagnetic filling formed by cellular base stations with total intensity of an electromagnetic background, formed by this stations at a terrestrial surface, and also with probability of hitting of building location into the restriction area of the nearest base station are received. The equations describing the restrictions on maximum permissible parameters of radio electronic environment, created by base stations at valid restrictions on maximum permissible levels of electromagnetic fields for the population are resulted.